Modulation of immune gene expression profile in Labeo catla with chronic toxicity to emerging endocrine disruptors through a multiorgan approach - Basanta Kumar Das; Suvra Roy; Vikash Kumar; Anupam Adhikari; Satabdi Ganguly; Kampan Bisai (Scientific Reports)
Abstract Endocrine-disrupting chemicals (EDCs) in the aquatic environment are an emerging concern and can lead to adverse health effects on humans and aquatic life. EDCsare ubiquitous in several daily use and personal care products and ubiquitous in aquatic ecosystems. The aquatic ecosystems also serve as major sinks of EDCs and have even been found to accumulate in aquatic organisms. Fish are an important sentinel species in the aquatic system and are a reliable indication of environmental water pollution. In the present study, we have assessed the immunotoxicity effects of three important EDCs, i.e., triclosan (TCS), bisphenol A (BPA), and diethyl phthalate (DEP). There is mounting evidence that EDCs impact several physiological systems, including fish immune systems. Hence, to better understand the immune system’s complexity, we have investigated how EDCs alter the immune responses and can aggravate immunotoxicity using Labeo catla as a model fish species. The results showed significant upregulation of immune gene expression; exposure to EDCs differentially modulates immunity across the different organs (liver and brain) of Labeo catla. The present study highlighted that endocrine-disrupting compounds (TCS, BPA, and DEP) have a significant immunotoxicity effect in fish and activate several immunological pathways to control the toxic effect and maintain homeostasis. The results also indicate that immune genes can be used as a biomarker for EDC toxicity. However, further studies need to see how immune-disrupting effects happen at actual exposure levels in the environment to EDCs.